EVALUATION OF LOCALLY RICE SEEDS HEALTH - Tri Martini Patria; Evy Pujiastuti; Siti Nurhaeni; Mekky Kusuma Dewi; Nur Indrayati Praba Ningrum; Mansyur Mansyur (Agric, 2022)
Seed health is one of the important factors in maintaining seed quality. This factor is very influential both during seed storage, plant growth in the field, and production to be produced. Seed can be one of the effective media in the spread of plant diseases. With the consideration that pathogenic seed transmission plays an important role in the spread and development of epidemic diseases in some commodities, then gradually seed health tests need to be incorporated into the seed certification process. Seed health testing is required to detect the presence of pathogens or seed health status. To support the program of activities of the Ministry of Agriculture in the development of local rice, it is necessary to start by evaluating the health of seeds in the local paddy varieties. The purpose of the research includes detecting the type of pathogens carried by local varieties in several provinces and inventories of pathogen data carried by local varieties of rice seeds circulating in several provinces. The research method was conducted by taking samples directly from the field and conducting DNA isolation by PCR test to detect bacteria Xanthomonas oryzae pv oryzae (Xoo) and Burkholderia glumae (BG) as well as the growth of pathogen samples in the laboratory. The results of identification are known some seeds detected bacteria Xanthomonas oryzae pv. oryzae (Xoo) and Burkholderia glumae (BG)) which is characterized by the emergence of DNA bands PCR amplification results in positive control according to DNA Ladder. The results of the identification of pathogenic fungi, known the presence of fungi causing blast disease (Pyricularia oryzae) in the overall example of rice seeds tested (47 examples of local rice seeds upland and local swamp) and there are 15 examples or 32% infected with a percentage of infections 0.25 - 14.75%. While result identification of nematodes, known the presence of parasitic nematode Aphelenchoides besseyi on the overall sample of local rice seeds tested (42 examples of local rice seeds upland and local swamp), with 25 examples or 59.5% infected with an infection range of 1-44 specimens.